Psycholinguistic Peculiarities of Individual Speech under Stress - Solovei, Oksana (Psychological Prospects Journal, 2014)
The article deals with the results of theoretical and empirical research of psycholinguistic features of the personality’s speech in situation of emotional stress. The relevance of the chosen problem is argued by author, its lack of elaborated is indicated both in theoretical and applied aspects. The review of the recent scientific research of domestic and foreign scholars is carried out in the field. The expediency of feasibility the research of personality’s speech in the situation of emotional stress is analyzed and substantiated on phonetic, lexical and syntactic levels. The research was conducted in Lesya Ukrainka EasternEuropean University, sample was made by the students of Psychology department. The article contains the description of theoretical and empirical methods, which were used to implement the tasks of this research. The description and justification of the results of this study contains the overview and interpretation of received data of comparative analysis of spontaneous neutral and spontaneous emotional speech of students. The empirical study of the personality’s speech in the situation of emotional stress allowed to set its features: the increase in the number of searching words; the selection of more stereotypical dictionary; the appearance of junk words; the choice of words with a clear positive or negative connotation; the increase the use of particles and interjections; the semantically irrelevant the repetitive of phrases, parts of phrase, single words, syllables; the incompleteness of words, sentences and increased number of self-correction; the appearance of unjustable and, probably, not perceived by the speaker the errors of concordance language units.